Effect of Financial Literacy, Income and Risk Perception on Investment Decision Making With Financial Behavior as Moderating Variable: Pengaruh Literasi Keuangan, Pendapatan dan Persepsi Resiko Terhadap Pengambilan Keputusan Investasi dengan Perilaku Keuangan Sebagai Variabel Moderasi - Suriansyah, Noorgina Sahiya; Harianto, Wiwit (Universitas Muhammadiyah Sidoarjo, 2022)
The purpose of this study is to determine the effect of the moderating variables of Financial Behavior in Financial Literacy, Income and Risk Perception on Investment Decision Making in the Capital Market. The population in this study were students of the 6th and 8th semesters of accounting study program at Muhammadiyah University of Sidoarjo, with a total population of 980 and a sample 71 respondents obtained by Simple Random Sampling. By using data analysis techniques in the form of Outer Model for testing the validity an reliability of data an Inner Model for hypothesis testing using the SmartPLS version 3.0 application. The results obtained prove that Financial Literacy and Income cannot be moderated by Financial Behavior on Onvestment Decision Making in the Capital Market. This is different from Risk Perception which can be moderated by Financial Behavior. So that it can strengthen the relationship between Risk Perception and Investment Decision Making in the Capital Market.